Community Empowerment through Cultivating Chili Trees as an Alternative Income Solution in Kramatwatu Village, Serang Regency - Edward Fazri; Esti Utami Pratiwi; Nora Asriani; Siti Sofiyah; Ikbal Nidaudin (EQUATOR SINAR AKADEMIA, 2023)
Community Empowerment through Chilli Tree Cultivation in Kramatwatu Village aims to provide an alternative source of income to improve living standards in the face of economic turbulence. This activity is carried out using training methods for planting, caring for and distributing the results. The series of activities starts from selecting local potential, selecting and procuring chili seeds, chili cultivation training, monitoring results, harvesting and distribution. This activity has an impact on increasing the community's alternative sources of income through the development of local food crops so that they can provide new enthusiasm in improving the standard of living.